PROTEST AND CONSUMER: A CONTENT ANALYSIS OF EBSCO ELECTRONIC DATABASE ACROSS 50 YEARS - A. Hendarto, Kresno; Dharmmesta, Basu S.; Purwanto, B.M.; Moeliono, Moira M.M. (Jurnal Komunitas: Research and Learning in Sociology and Anthropology, 2013)
AbstractThe objective of this research is to review the articles of protest and consumer in EBSCO electronic journal. The objective will be achieved by answering the following questions: (i) what is the method of reviewed articles with the topic of protest; and (ii) what agenda of future research? The results showed that most reviewed articles Â used qualitative approach. Most research are empirical in nature. For articles of empirical research, most of the data were obtained through observation and were analyzed descriptively. Literature on protest and consumer can be classified into 3 main categories: (1) discussing about the frequency, cause, and objective of protest; (2) discussing about the consequence of protest; and (3) discussing about the Â motivation of individuals in taking part in the protest. This review also showed that there are major gaps from the previous research including the fact that attitude is not the focal point in explaining why consumers take part in protest and no article discussed consumersâ attitude to the object taking part in the protest. Â AbstrakTujuan penelitian ini adalah melakukan ulas balik artikel-artikel bertopik protes dan konsumen pada database elektronik EBSCO. Tujuan tersebut akan dicapai dengan menjawab pertanyaan penelitian sebagai berikut: (i) apa metode dan sifat dasar dari artikel yang bertopik protes; dan (ii) agenda penelitian apa yang masih terbuka ke depan? Hasil analisis menunjukkan bahwa kebanyakan artikel yang direview menggunakan pendekatan kualitatif. Kebanyakan artikel merupakan penelitian empiris. Untuk artikel penelitian empiris, mayoritas data diperoleh dengan cara observasi, dan dianalisis secara deskriptif. Literatur tentang protes dan konsumen dapat digolongkan dalam 3 bagian besar, yaitu (1) yang membahas tentang frekuensi, sebab, dan tujuan protes; (2) yang membahas tentang konsekuensi dari protes; dan (3) yang membahas tentang motivasi individu yang mendasari untuk berpartisipasi dalam protes. Ada beberapa kesenjangan dalam penelitian-penelitian Â sebelumnya, diantaranya adalah bahwa sikap bukan merupakan fokus dalam menjelaskan mengapa konsumen melakukan protes dan belum ada dari artikel tersebut yang melihat sikap konsumen terhadap objek yang melakukan protes.Â Â© 2013 Universitas Negeri Semarang